A computational bioinformatics analysis of gene expression identifies candidate agents for prostate cancer. (24th June 2013) - Wen, D.; Geng, J.; Li, W.; Guo, C.; Zheng, J.
Summary Prostate cancer is the second most frequently diagnosed cancer and the sixth leading cause of cancer death in males worldwide. Although great progress has been made, the molecular mechanisms of prostate cancer are far from being fully understood and treatment of this disease remains palliative. In this study, we sought to explore the molecular mechanism of prostate cancer and then identify biologically active small molecules capable of targeting prostate cancer using a computational bioinformatics analysis of gene expression. A total of 3068 genes, involved in cell communication, development, localisation and cell proliferation, were differentially expressed in prostate cancer samples compared with normal controls. Pathways associated with signal transduction, immune response and tumorigenesis were dysfunctional. Further, we identified a group of small molecules capable of reversing prostate cancer. These candidate agents may provide the groundwork for a combination therapy approach for prostate cancer. However, further evaluation for their potential use in the treatment of prostate cancer is still needed.